National Mortality Followback Survey, 1993 ([Verlag nicht ermittelbar], 2000)
The National Mortality Followback Survey (NMFS) Program, begun in the 1960s by the National Center for Health Statistics (NCHS), uses a sample of United States residents who die in a given year, supplementing information derived from the death certificate with information from the next of kin or another person familiar with the decedent's life history. This information, sometimes enhanced by administrative records, is collected in order to study the etiology of disease, demographic trends in mortality, and other health issues. The 1993 National Mortality Followback Survey (NMFS) sampled individuals aged 15 years and over who died in 1993. Forty-nine of the 50 state vital registration areas, as well as the independent vital registration areas of the District of Columbia and New York City, granted approval to sample their death certificates. (South Dakota declined to participate due to a state law restricting the use of death certificate information.) A sample of 22,957 death certificates from 1993 was then drawn. To obtain reliable numbers for important population subgroups, such as persons under age 35, women, and the Black population, death certificates from those subgroups were oversampled. The 1993 NMFS survey focused on five subject areas: (1) socioeconomic differentials in mortality, (2) associations between risk factors and cause of death (use of tobacco, alcohol, drugs, firearms, motor vehicles), (3) disability (medical condition and cognitive functioning during the last year of life), (4) access and utilization of health care facilities during the last year of life (number of doctor visits, days bedridden, nursing home experiences, use of assistive medical devices, availability of health insurance), and (5) reliability of certain items reported on the death certificate. Demographic variables include age, gender, race, marital status, birthplace, education, occupation and industry, and income and assets. The 1993 NMFS survey differed from the previous mortality followback surveys in several ways: First, it emphasized deaths due to homicide, suicide, and unintentional injury. Second, the subject areas were considerably broader (many previously-surveyed subject areas, however, are included for trend analysis). This survey was also the first to acquire national-level information from medical examiners and coroners. Finally, the complexity of the questionnaire necessitated telephone or in-person interviews. The 1993 NMFS was designed in collaboration with other agencies of the Public Health Service, Department of Health and Human Services, and the National Highway Traffic Safety Administration.